2019
DOI: 10.1200/po.18.00229
|View full text |Cite
|
Sign up to set email alerts
|

Application of Circulating Cell-Free Tumor DNA Profiles for Therapeutic Monitoring and Outcome Prediction in Genetically Heterogeneous Metastatic Melanoma

Abstract: PURPOSE Circulating cell-free tumor DNA (ctDNA) reflects the heterogeneous spectrum of tumor-specific mutations, especially in systemic disease. We validated plasma-based assays that allow the dynamic quantitative detection of ctDNA as a prognostic biomarker for tumor load and prediction of therapy response in melanoma. MATERIALS and METHODS We analyzed plasma-derived ctDNA from a large training cohort (n = 96) of patients with advanced-stage melanoma, with assays for the BRAFV600E and NRASQ61 driver mutations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(62 citation statements)
references
References 21 publications
4
57
1
Order By: Relevance
“…We observed that undetectable ctDNA at 6–8 weeks of therapy predicted longer PFS, verifying that ctDNA can be a valuable biomarker in melanoma patients receiving checkpoint inhibitors. This is in agreement with other studies showing that ctDNA is a predictor for PFS in melanoma patients treated with checkpoint inhibitors but also targeted therapy [ 12 , 13 , 15 , 16 , 41 ]. We did not find an association between ctDNA detection at baseline and PFS, a finding that is both in agreement with [ 13 ] and in contrast to findings of other studies [ 12 , 14 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We observed that undetectable ctDNA at 6–8 weeks of therapy predicted longer PFS, verifying that ctDNA can be a valuable biomarker in melanoma patients receiving checkpoint inhibitors. This is in agreement with other studies showing that ctDNA is a predictor for PFS in melanoma patients treated with checkpoint inhibitors but also targeted therapy [ 12 , 13 , 15 , 16 , 41 ]. We did not find an association between ctDNA detection at baseline and PFS, a finding that is both in agreement with [ 13 ] and in contrast to findings of other studies [ 12 , 14 ].…”
Section: Discussionsupporting
confidence: 93%
“…Analysis of ctDNA can identify tumor-specific mutations and has been shown to correlate with tumor burden and clinical outcome [ 9 , 10 ]. Several studies have found that undetectable ctDNA prior to or early after initiating treatment is associated with improved progression-free survival (PFS) and OS [ 11 , 12 , 13 , 14 , 15 , 16 ]. Furthermore, ctDNA can also be used to uncover mechanisms of acquired resistance at the time of disease progression, allowing therapy to be adapted accordingly [ 12 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the minimally invasive nature of liquid biopsy overcomes these issues. Recent studies have shown the potential of genomic analysis of plasma cell-free DNA (cfDNA) to facilitate early cancer detection (Bettegowda et al, 2014;Cree et al, 2017;Lam et al, 2018), residual disease detection (Chaudhuri et al, 2017;Tie et al, 2016), and disease and treatment monitoring (Demuth et al, 2018;Long-Mira et al, 2018;V araljai et al, 2019) that could lead to the era of precision oncology.…”
Section: Introductionmentioning
confidence: 99%
“…A study reported a correlation between alterations in the ctDNA levels during therapy and the tumor response, with an increase in the levels being predictive of disease progression and a decrease being predictive of treatment response. Detection of NRAS Q61 ctDNA in the baseline samples of patients with BRAF V600E mutation who were treated with MAPK inhibitors was reported to be associated with shorter PFS [119]. Another recent study corroborated this finding by demonstrating that increasing levels of ctDNA during melanoma treatment with targeted therapy or immunotherapy could predict disease progression prior to the progression becoming apparent in radiological imaging [120].…”
Section: Melanomamentioning
confidence: 89%
“…Interestingly, a recent study reported plasma-based comprehensive genomic sequencing of 8,388 consecutively-tested advanced NSCLC using the NGS platform Guardant 360 [115]. The ctDNA analysis revealed somatic alterations in 86% of these cases, with the identification of therapeutically targetable and resistant mutations [119]. On the basis of these data, the use of comprehensive ctDNA testing was proposed for the NSCLC patients who are incompletely tested at the time of diagnosis and for those who are in progression on targeted therapies [115].…”
Section: Lung Cancermentioning
confidence: 99%